Pengelolaan Arsip Dinamis Aktif di Kantor Cabang Perum Pengadaian Marapalam Padang - Rahmadeni, Rico; Syahyuman, Syahyuman (Ilmu Informasi Perpustakaan dan Kearsipan, 2012)
The purpose of writing this paper is twofold. First, describe the storage system records active in Padang Marapalam Pawnshop Branch. Second, describe the procedure active records storage Pawnshop Branch Marapalam Padang. From the above analysis, we can conclude (1) archival storage systems in office Pawnshop Marapalam Padang has not been done properly in archival science, (2) storage procedures performed by the group archives incoming and outgoing mail, put the files in the binder holes (Ordener), and save the file in the archive storage cabinets. From these data can be implemented to Marapalam Pawnshop Branch Padang that: (1) archival storage system equipped with a storage system in chronological order, (2) having a berkependidikan chancery clerk, and the clerk should be more careful in conducting archival storage and clustering. Keywords: records; records active